FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS SIDOMULYO RAWAT JALAN - Okmaladewi, Wan Maulina; Lapau, Buchari; Rienarti Abidin, Aldiga (Ensiklopedia of Journal, 2024)
At the Sidomulyo Health Center the incidence of dengue fever were 256 cases from 2017 to 2021. The purpose of research was find  factors that influence the incidence of dengue fever in Sidomulyo Health Center working area. The method of research is quantitative with a case control study design, the interviews with structured way. Data analysis used univariate, bivariate, multivariate with multiple logistic regression analysis. The results showed the presence of garbage affected 2.3 times (95% CI: OR = 1.06–5.15) the incidence of dengue fever compared to no garbage, the presence of confounding waste on the presence of Aedes aegypti larvae, used mosquito net on ventilation, nap habits, and garden plants affected 2 times (95% CI: OR=1.30-3.10) the incidence of dengue fever when compared with no garden plants. It can be concluded that necessary to strengthen environmental health programs to eradicate waste and provide health education to peoples about nap habits against dengue fever, kill the Aedes aegypti larvae, used mosquito net on ventilation, and replace the plants with Aedes aegypti mosquito repellent.Keywords: Dengue Fever, Garbage, Aedes Aegypti